Probiotic Lactobacillus spp. improves Drosophila memory by increasing lactate dehydrogenase levels in the brain mushroom body neurons - Shuk-Man Ho; Wan-Hua Tsai; Chih-Ho Lai; Meng-Hsuan Chiang; Wang-Pao Lee; Hui-Yu Wu; Pei-Yi Bai; Tony Wu; Chia-Lin Wu (Gut Microbes, 2024)
Probiotics are live microorganisms that offer potential benefits to their hosts and can occasionally influence behavioral responses. However, the detailed mechanisms by which probiotics affect the behavior of their hosts and the underlying biogenic effects remain unclear. Lactic acid bacteria, specifically Lactobacillus spp. are known probiotics. Drosophila melanogaster, commonly known as the fruit fly, is a well-established model organism for investigating the interaction between the host and gut microbiota in translational research. Herein, we showed that 5-day administration of Lactobacillus acidophilus (termed GMNL-185) or Lacticaseibacillus rhamnosus (termed GMNL-680) enhances olfactory-associative memory in Drosophila. Moreover, a combined diet of GMNL-185 and GMNL-680 demonstrated synergistic effects on memory functions. Live brain imaging revealed a significant increase in calcium responses to the training odor in the mushroom body β and γ lobes of flies that underwent mixed feeding with GMNL-185 and GMNL-680. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) and whole-mount brain immunohistochemistry revealed significant upregulation of lactate dehydrogenase (LDH) expression in the fly brain following the mixed feeding. Notably, the genetic knockdown of Ldh in neurons, specifically in mushroom body, ameliorated the beneficial effects of mixed feeding with GMNL-185 and GMNL-680 on memory improvement. Altogether, our results demonstrate that supplementation with L. acidophilus and L. rhamnosus enhances memory functions in flies by increasing brain LDH levels.